Importancia de la lámina de agua en el cultivo de arroz para su desarrollo y producción sostenible - Mora Ramírez, Victor Adonis (2024)
Rice cultivation represents a fundamental pillar in agricultural and food history, rooted in centuries-old practices that position it as an essential component in food security and economic development, as its adaptability to diverse environments and climatic conditions makes it a versatile crop, capable of thriving in both flooded lands and rainfed systems, given its economic and food relevance rice is undeniable, but also drives local and global economies, generating employment and contributing significantly to the gross domestic product of many countries, The development process of rice cultivation encompasses several stages, from planting to harvest, where factors such as water management, fertilisation and pest control are critical to ensure optimal yields, with the presence of a sheet of water in the rice fields playing a crucial role in this process, acting as a key element in crop management by controlling weeds, regulating soil temperature and improving nutrient availability, hence proper management of the water table, through different types of flooding and drainage practices, is essential to ensure the sustainability and productivity of rice cultivation in various regions of the world, including Ecuador, where climatic and soil diversity has led to the cultivation of a wide range of varieties.